Comparative performance between natural Endospermum diadenum (Miq.) airy shaw wood and treated wood impregnated with Nanoclay and Phenolic resin - Leemon, Nabil Fikri (2015)
Sesenduk (Endospermum diadenum) is a low density tropical hardwood that has not been fully utilized due to their poor properties in nature. One of the potential ways to improve its properties is through bulking treatment with phenol formaldehyde resin followed by either heating or compressing at high temperature. However, the treated materials release high formaldehyde when treated with low molecular weight phenol formaldehyde (LmwPF). Attempts to reduce formaldehyde emission by incorporating urea in the treatment system have been explored and the results showed that the treated material release lower formaldehyde emission compared to those treated without urea. However, some of the physical and mechanical properties were lower compared to the latter. Incorporation of nano particle to the phenolic matrix could possibly reduce the use of high concentration LmwPF in the treatment system and as a result would lower the formaldehyde emission. In addition, the properties of the treated could be better enhanced. The aim of the study are to examine the characteristics of LmwPF resin and nanoclay admixture and to determine its effects on the performance of impreg wood. Montmorillonite nanoclay nanomer (0.5%-1.5% w/w based on solid PF) was dispersed in LmwPF resin (10%-25% w/v) using ultrasonication technique. The dispersion of nanoclay in LmwPF was examined using X-ray diffractometer (XRD) and Transmission electron microscopy (TEM). XRD and TEM analyses confirmed that the nanoclay dispersion in the resin was in exfoliated form. The results also showed that pH value were significantly affected by the addition of nanoclay in the PF resin. The gelling time of the admixture was reduced as the nanoclay content in the admixture increased. Air-dry sesenduk (Endospermum diadenum) wood was impregnated with these admixtures using vacuum pressure process followed by curing at 1500C for 30 min. The strength properties, dimensional stability and formaldehyde emission were evaluated and compared with impreg wood treated with LmwPF per se. Scanning electron micrograph (SEM) showed that the admixture penetrated the wood cell wall to some extend but larger amount polymer matrix was found resided in the cell lumen. The results showed that the polymer retention and density of the admixture-impregnated samples were higher than the PF impregnated samples. This admixture had successfully bulked the cell wall of the wood and imparted higher dimensional stability. The modulus of rupture (MOR) and modulus of elasticity (MOE), compressive stress and hardness of the admixture-impregnated wood were more superior to the PF-impregnated wood. The admixture was also found able to reduce the formaldehyde emission of the admixture-impregnated wood by 3-5% compared to PF-impregnated wood. The durability of treated sesenduk wood against white-rot fungus (Pycnoporous sanguineus) and subterranean termites (Coptotermes curvignathus Holmgren) was evaluated based on weight loss after exposure for 16 weeks and 4 weeks, respectively. The results showed that wood treated with PF and PF/nanoclay admixture increased the resistance of the wood. For fungal decay test, the weight loss for PF impregnated wood ranged from 2.24%-4.85% and admixture impregnated samples from 2.11%-4.74%. The weight loss for untreated wood was 31.86%. A similar trend was also observed for the test against termite. The weight loss value ranges from 0.49%-3.40% and 0.37%-3.20% for wood treated with PF and admixture-impregnated wood compared with untreated wood (17.95%) respectively.